2015
DOI: 10.1557/jmr.2015.382
|View full text |Cite
|
Sign up to set email alerts
|

Wear mechanism of coated and uncoated carbide cutting tool in machining process

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Also, a correlation between the applied cutting speed and the cutting tool life was studied to reveal cutting speed influences on the machinability process. Ghani 2 International Journal of Manufacturing Engineering et al studied the machinability of Inconel 718 and Metal Matrix Composite (MMC) alloys using vertical and down milling operations [6]. Their study included the investigation of the formed wear on carbide cutting tool edges.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a correlation between the applied cutting speed and the cutting tool life was studied to reveal cutting speed influences on the machinability process. Ghani 2 International Journal of Manufacturing Engineering et al studied the machinability of Inconel 718 and Metal Matrix Composite (MMC) alloys using vertical and down milling operations [6]. Their study included the investigation of the formed wear on carbide cutting tool edges.…”
Section: Introductionmentioning
confidence: 99%
“…When the working on the titanium alloy the tool wear gradually increased after the damage of the coating surface. Various researchers suggested that use only coated insert for machining of titanium alloy [1,4]. Basically, two types of coating (CVD & PVD) used during the machining of hard materials.…”
Section: Application Of Cutting Tools and Cooling Techniquesmentioning
confidence: 99%
“…At elevated temperature, a chemical reaction takes place between the tool and workpiece causes the wear in tools also chips affected the rake surface of the tools. Mainly flank wear (adhesion), notch wear and crater wear (diffusion) produce during the machining of Ti-6Al-4V ELI alloy [4,5]. Sulaiman et al [1] analysed the tool wear rate for an uncoated tool insert during high speed turning of Ti-6Al-4V ELI alloy in a dry environment.…”
Section: ''""mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies [7][8][9][10] have shown that the chipping and breakage of the tool are the major failure modes during machining, including milling, of nickel-based superalloys using WC-Co tools. The progression of tool failure during the milling of a nickel-based superalloy (718Plus), using an ordinary milling condition, has been characterised and explained [11].…”
Section: Introductionmentioning
confidence: 99%